Gaucher Disease Types I and III Responded Well to Substrate Reduction Therapy Using Eliglustat - Harai, Nozomi; Kawaguchi, Yoshihiko; Hanihara, Mitsuto; Ichijo, Masashi; Ichikawa, Daisuke; Uchinuma, Hiroyuki; Tsuchiya, Kyoichiro (Internal Medicine, 2023)
Gaucher disease (GD) causes the accumulation of glucocerebrosides in various organs, resulting in hepatosplenomegaly, anemia, decreased platelet counts, and bone disorders. Glucosylsphingosine accumulates in the brain and causes central nervous system (CNS) disorders. GD can be classified into types I (without CNS disorders), II, and III. Substrate reduction therapy (SRT) is an oral therapy that improves patients' quality of life; however, its effect on type III GD is unknown. We administered SRT to GD types I and III patients and found it effective. Malignancy is a late complication of GD, but this is the first report of Barrett adenocarcinoma.